A Descriptive Study Regarding Awareness and Practices Menstruation among Adolescent Girls in Rewa City, Madhya Pradesh, India - Asati, Alka Modi; Singh, Sandeep; Jain , Chakresh; Mishra, Anvita (Current Innovations in Medicine and Medical Science Vol. 6, 2022)
The present study highlights the importance of adolescent girls receiving adequate knowledge about menstruation before menarche through menstrual hygiene management programmes in schools. Adolescence, as defined by the World Health Organization, is from 10 to 19 years old. According to the most current census in 2011, there are 253 million adolescents in India, or 25 percent of the entire population. A girl's menarche marks the start of her reproductive life and is a significant life milestone. For many girls, menstruation presents a challenge since a lack of sanitary items limits their participation in social and educational activities. A cross-sectional study was carried out among 200 adolescent girls of 9th to 12th standard classes in schools of Rewa, Madhya Pradesh, India. A semi-structured questionnaire was used to collect data after obtaining permission from the school Principals and informed consent from parents. The objectives, methods and implications of the study were explained to participants. Mean age of the participants was 15.1 ± 1.54 years and mean age of menarche was 13.24±1.20 years. Most (68.5%) girls had heard about menstruation before menarche; 91.5% answered that menstruation is a normal phenomenon; 87% used single-use disposable sanitary pads and 6.5% used washable, reusable cloths. This study recommends that menstrual hygiene, health and sex education programmes be conducted at schools and also at primary care level, delivered by trained healthcare professionals. This study reinforces the need to empower young girls and to bring them out of traditional beliefs, taboos, misconceptions and restrictions to further improve the overall picture of menstrual health. Males and females in the community should be educated.